Non-CG methylation and multiple histone profiles associate child abuse with immune and small GTPase dysregulation - Pierre‐Eric Lutz; Marc-Aurèle Chay; Alain Pacis; Gary G. Chen; Zahia Aouabed; Elisabetta Maffioletti; Jean‐François Théroux; Jean‐Christophe Grenier; Jennie Yang; Maria L. Aguirre; Carl Ernst; Adriana Redensek; et al. (2021)
Abstract Early-life adversity (ELA) is a major predictor of psychopathology, and is thought to increase lifetime risk by epigenetically regulating the genome. Here, focusing on the lateral amygdala, a major brain site for emotional homeostasis, we describe molecular cross-talk among multiple mechanisms of genomic regulation, including 6 histone marks and DNA methylation, and the transcriptome, in subjects with a history of ELA and controls. In the healthy brain tissue, we first uncover interactions between different histone marks and non-CG methylation in the CAC context. Additionally, we find that ELA associates with methylomic changes that are as frequent in the CAC as in the canonical CG context, while these two forms of plasticity occur in sharply distinct genomic regions, features, and chromatin states. Combining these multiple data indicates that immune-related and small GTPase signaling pathways are most consistently impaired in the amygdala of ELA individuals. Overall, this work provides insights into genomic brain regulation as a function of early-life experience.